Enhancement Image Compression using the Average Filtering and DCT - Ezzedin Muftah Enbiah; Khaled Almarimi; Moammer H. Daw; Belgasem Alwerfali (African Journal of Advanced Pure and Applied Sciences, 2024)
Despite all the advances in storage and digital communication, the rapidly increasing volume of multimedia data continues to tax available resources. Compression of images becomes highly imperative to deal with the situation because of reduced requirements in terms of storage and transmission bandwidth while keeping the perceptible quality of the images. Among the lossy compression techniques for image compression, DCT-based block coding finds extensive application. However, it often causes highly perceived artifacts, mainly blocking effects, at higher compression rates. This research is conducted to minimize blocking artifacts generated by DCT-based image compression. The beginning gives an overview of data compression and the existing deblocking methods. Then it delves into DCT-based image compression and proposes a simple and effective solution to the blocking problem, depending on filtering the pixel value at the boundaries between the blocks. We test our proposed technique on different test images and analyze the results to know its effectiveness.